2022
DOI: 10.1001/jamaoto.2022.1210
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Sleep Features, Mental Health Outcomes, and Alcohol and Tobacco Consumption in Residents and Fellows in Otolaryngology Before and During the COVID-19 Pandemic

Abstract: The workload of many residents and fellows in otolaryngology-head and neck surgery has particularly increased during the COVID-19 pandemic; however, outcomes associated with mental health status and sleep remain unclear.OBJECTIVE To assess the sleep, mental status, and alcohol and tobacco consumption habits of residents and fellows before the COVID-19 pandemic (before March 10, 2020) and during the pandemic period (after March 10, 2020). DESIGN, SETTING, AND PARTICIPANTSThis cohort study included residents and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…To the Editor We were pleased to read the recent article by Chebib et al 1 The effects of COVID-19 on resident physician training are not yet fully understood and present a wide range of effects, from issues in educational objectives to mental distress. There is some evidence pointing out that younger and less experienced health professionals, such as resident physicians, are more prone to suffer mental distress when facing unforeseen situations, such as the COVID-19 pandemic.…”
Section: Psychological Issues and Alcohol Consumption In Resident And...mentioning
confidence: 99%
See 2 more Smart Citations
“…To the Editor We were pleased to read the recent article by Chebib et al 1 The effects of COVID-19 on resident physician training are not yet fully understood and present a wide range of effects, from issues in educational objectives to mental distress. There is some evidence pointing out that younger and less experienced health professionals, such as resident physicians, are more prone to suffer mental distress when facing unforeseen situations, such as the COVID-19 pandemic.…”
Section: Psychological Issues and Alcohol Consumption In Resident And...mentioning
confidence: 99%
“…In fact, being a resident seems to be a risk factor for substance misuse, 4 as well as having a heavy workload. 1 Both substance misuse and mental distress in health care workers are associated with suboptimal patient care.…”
Section: Psychological Issues and Alcohol Consumption In Resident And...mentioning
confidence: 99%
See 1 more Smart Citation
“…Burnout can threaten care quality, patient safety, and has had detrimental effects on the healthcare system [ 4 , 5 ]. Resident burnout increased during COVID-19 with up to 45% of residents self-reporting poor sleep quality, increased workload, and sleep deprivation during the pandemic [ 1 , 2 , 6 , 7 ]. As many as half of physicians had a self-reported sleep disorder or excessive sleepiness during this time [ 6 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The increase in workload during the pandemic reported by Chebib et al also should be an alarming sign of a poor experience for resident physicians in terms of learning. This rise probably was not owing to their usual otolaryngology–head and neck surgery activities, and recent evidence has shown that increased workload is associated with impaired learning in resident physicians, independent of the training area.…”
mentioning
confidence: 99%